Pidgin, lingua franca, sabir - terminological study - Hlibowicka-Węglarz, Barbara (Romanica Olomucensia, 2016)
The terms pidgin, lingua franca and sabir appear very often in the sociolinguistic literature; however, they are not properly defined. Therefore, the aim of this paper is to define the complexity of the reality which accompanies the formation and functioning of the above-mentioned linguistic phenomena. Moreover, characteristic features of each of these forms are presented in this study to emphasise the similarities and differences between them.
Keywords: pidgin; lingua franca; vehicular languages; Creole languages; sociolinguistic.